STRATEGIC MANAGEMENT OF CHANGE IN ISLAMIC EDUCATION INSTITUTIONS (A Case Study at Islamic Education Institution of Syafana Islamic School Serpong) - Eva Iryani; M. Masruri; Maisah (Dinasti Publisher, 2021)
This paper shows the role of Syafana Islamic School's strategic management in the transformation of the implementation of the full-day program by changing it to a boarding school system. These changes are not only in the aspect of the learning system, but even on the curriculum side which uses the combination of several curricula; Diknas, Egypt (Al-Azhar) and Cambridge are integrated into the concept of Islamic boarding school, the change process is observed and analyzed using the SWOT analysis model (Strength, Weakness ,Opportunity and Threath) with an emphasis on the process of changing the system and curriculum applied by Syafana Islamic School. With the results and findings, there is a strategic management in the transformation by integrating and using four collaborative strategies. First, the Strategic Opportunity Strategy. With the model of merging and accumulating strengths by exploiting various opportunities. Second, the Strength Threath Strategy with knowledge of the strengths possessed can see and anticipate existing threats. Third, the Weakness Opportunity Strategy, the opportunity to be a major factor in efforts to overcome the weaknesses in this institution and Finally the Weakness Threath Strategy. Defense efforts are still analyzed and carried out in order to minimize weaknesses and threats from outside the institution.